EVALUATION OF REGIONAL LAND SUITABILITY SETTLEMENTS IN SOLOK CITY - Annur, Latifa; Umar, Iswandi (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
This study aims to 1) determine the suitability of land in Solok City, 2) determine the suitability of settlement land suitability with the RTRW in Solok City, 3) determine the suitability of settlement land suitability with the existing conditions of Solok City. The data analysis technique used is the Scoring and overlay method using ArcGIS 10.4 software. The results of the study 1) the suitability of residential land in Solok City has 3 classes, namely according to 183Ha (3.18%) , marginally suitable 4496 Ha (78.36%) and not suitable 1058 (18.44Ha%). 2) evaluation of the suitability of residential land with the RTRW of Solok City in 2012-2031 which has a total area of ​​1786 Ha, there are slight differences in the inappropriate class of 29 Ha (1.62%) and dominated by marginally suitable class of 1723 Ha (96.47%) scattered in the Tanjung Harapan District 3) evaluation of land suitability with existing land use in 2021 found a slight difference in the inappropriate class of 25Ha (4.09%) and dominated by marginally suitable class with an area of ​​577Ha (94.43%).